Pressure-induced transformations during annealing of silicon implanted with oxygen - Misiuk, A.; Efros, B.M. (Физика и техника высоких давлений, 2006)
Enhanced hydrostatic pressure (HP, up to 1.5 GPa) applied during annealing at up to 1570 K (HT) of silicon with oxygen introduced by implantation (Si:O), exerts pronounced effect on the transformation of oxygen admixture. In particular, HP affects the microstructure of Si:O and a creation of oxygen-enriched (for implanted oxygen dose, D ≤ 1·10¹⁷ cm⁻²) or continuous (for D ≥ 6·10¹⁷ cm⁻²) buried SiO2 layers. Numerous treatment parameters contribute to the HP-induced phenomena in processed Si:O, among these are the HPaffected mobility and solubility of implanted oxygen as well as of silicon interstitials and of other implantation-induced defects and so the stability of oxygen clusters/precipitates; the misfit at the SiO₂/Si boundary is tuned by HP.